Modelling the potential clinical and economic impact of universal antenatal hepatitis C (HCV) screening and providing treatment for pregnant women with HCV and their infants in Egypt: a cost-effectiveness study - Giuseppe Indolfi; Diana M Gibb; Sarah Pett; Yazdan Yazdanpanah; Sylvie Deuffic-Burban; Anthony E Ades; Karen Scott; Ali Judd; Nadia Hachicha-Maalej; Clotilde Lepers; Intira Jeannie Collins; Manal H El Sayed (BMJ Publishing Group, 2024)
Backgrounds and aims Pregnant women and children are not included in Egypt's hepatitis C virus (HCV) elimination programmes. This study assesses the cost-effectiveness of several screening and treatment strategies for pregnant women and infants in Egypt.Design A Markov model was developed to simulate the cascade of care and HCV disease progression among pregnant women and their infants according to different screening and treatment strategies, which included: targeted versus universal antenatal screening; treatment of women in pregnancy or deferred till after breast feeding; treatment of infected children at 3 years vs 12 years. Current practice is targeted antenatal screening with deferred treatment for the mother and child. We also explored prophylactic treatment after birth for children of diagnosed HCV-infected women. Discounted lifetime cost, life expectancy (LE) and disability-adjusted life-years (DALYs) were calculated separately for women and their infants, and then combined.Results Current practice led to the highest cost (US$314.0), the lowest LE (46.3348 years) and the highest DALYs (0.0512 years) per mother-child pair. Universal screening and treatment during pregnancy followed by treatment of children at 3 years would be less expensive and more effective (cost saving) compared with current practice (US$219.3, 46.3525 and 0.0359 years). Prophylactic treatment at birth for infants born to HCV RNA-positive mothers would also be similarly cost saving, even with treatment uptake as low as 15% (US$218.6, 46.3525 and 0.0359 years). Findings were robust to reasonable changes in parameters.Conclusion Universal screening and treatment of HCV in pregnancy, with treatment of infected infants at age 3 years is cost saving compared with current practice in the Egyptian setting.